2020
DOI: 10.5603/arm.a2020.0187
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ultrasonography in Assessment of Anatomic Upper Airway Changes in Patients with Obstructive Sleep Apnea

Abstract: Instroduction: Obstructive sleep apnea is a common disorder, characterized by recurrent narrowing and closure of the upper airway accompanied by intermittent oxyhemoglobin desaturation and sympathetic activation. Ultrasound imaging of the airways has advantages of being safe, quick, repeatable, portable and widely available. Airway ultrasound can visualize and assess the mouth and tongue, oropharynx, hypopharynx, epiglottis, larynx, vocal cords, cricothyroid membrane, cricoid cartilage, trachea, and cervical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Hussein et al showed a statistically significant increase in the lateral parapharyngeal wall thickness (LPWT) in OSA patients compared to controls [ 60 ]. Similarly, a statistically higher distance between lingual arteries (DLA) was also observed in OSA patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hussein et al showed a statistically significant increase in the lateral parapharyngeal wall thickness (LPWT) in OSA patients compared to controls [ 60 ]. Similarly, a statistically higher distance between lingual arteries (DLA) was also observed in OSA patients.…”
Section: Resultsmentioning
confidence: 99%
“…Hussein et al showed a statistically significant increase in the lateral parapharyngeal wall thickness (LPWT) in OSA patients compared to controls [60]. Similarly, a statistically In a more recent study, Molnár et al used a combination of US LPWT values and anthropometric parameters to achieve a 93% effectiveness in OSA prognostication in one hundred patients [58].…”
Section: Tonsilsmentioning
confidence: 99%